Drought risk, farmer communities’ perceptions and planning for resilience in rural Crete, Greece - Sapountzaki, Kalliopi; Daskalakis, Ioannis (AESOP, 2017)
Drought incidents may originate from both, manmade and natural factors and are characterized by uncertainty. The present paper attempts to shed light on the interrelations between exposure, drought perceptions and the adaptive responses opted by agents attempting to cope with drought risk and to provide insights into the planning processes implemented at the levels of the individual agents and the water management authorities. The choice of personal versus collective resilience strategies is largely a function of risk perception and the availability of resilience assets, but it is also a matter of power relations and alliance forging. The farming communities and the local self-government authorities of Messara plain in rural Crete provide the testbed on which the authors have attempted to scrutinize their initial assumptions by using appropriate questionnaires and interviews with key-staff of planning authorities.
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017